Polydopamine Functionalization: A Smart and Efficient Way to Improve Host Responses to e-PTFE Implants - Talon, Isabelle; Schneider, Anne; Ball, Vincent; Hemmerle, Joseph (Frontiers in Chemistry, 2019)
Among the different materials used as protheses for the treatment of Congenital Diaphragmatic Hernia, expanded polytetrafluoroethylene (e-PTFE) plays a leading role owing to its mechanical properties as explained in the first part of this review. However, this material is poorly cell adhesive, which is expected for its contact on the abdominal face, but should display specific tissue adhesion on its thoracic exposed faced. A side specific functionalisation method is hence required. The deposition of a nanosized polydopamine film on PTFE is known to be possible but immersion of the e-PTFE membrane in an aerated dopamine solution leads to a functionalisation not only on both faces of the membrane but also in its porous volume. The fact that polydopamine also forms at the water/air interface has allowed to transfer a polydopamine film on only one face of the e-PTFE membrane. The deposition method and applications of such Janus like membranes are reviewed in the second part of the review.